Personal Injury Claims (PIC) Database Modeling in Malaysia - Ruslawati Nik Mustapa, Nik; Awang Ali, Najihan; Husna Jamian, Nurul; Abdul Hamid, Hussin; Syaeda Mat Saleh, Syadatul; Baharain, Roziana (International Journal of Engineering and Technology, 2018)
Road accident often leads to claims for personal injury by aggrieved parties. In Malaysia, courts have been using multiplier-multiplicand approach. This approach seems to be outdated and unfair to the claimant. Presently, the approach excludes the claimant's personal condition in the calculation of quantum of damages. Hence, this study uses the Ogden Table as introduced in the United Kingdom as benchmarking guidelines, by taking into account of all aspect of claimant's personal condition for the purpose of such calculation. This study aim is to build upon a proposed data modeling system known as Entity Relationship Diagram (ERD) and the created process modeling known as data flow diagram (DFD). In so doing, the claimants will insert his input data, run it through the first process, and store the information in the claim injury part database. They can also edit and store to claim injury part database on their own. This will generate a report with the information in claim injury part database and can be viewed by claimant, court and lawyer as target users. It is hoped that it will facilitate the calculation of injury claim which would serve justice and accuracy of personal injury in road accidents.Â Â